THE CREATION OF THE BEDHAYA KETAWANG DANCE STORY BOOK AT SURAKARTA PALACE - Riyanto, Bedjo; Kartono, Jasmine Aurelia (ISI Press Institut Seni Indonesia Surakarta, 2023)
This study examines the Bedhaya Ketawang dance in relation to the cultural traditions of the Surakarta Palace in Indonesia. This research primarily seeks to elucidate the significance of introducing and preserving Javanese culture, which still adheres to established norms. This study employs a qualitative research approach, utilizing a literature review method and complemented by interviews focusing on the Bedhaya Ketawang dance. The audience's responses indicate a positive reception towards the illustrations that have been created. They could easily comprehend the material presented in the storybook, enabling them to articulate the uniqueness of the Bedhaya Ketawang dance and its significance.